The Pentateuch : introducing the Torah - Dozeman, Thomas B. (Introducing Israel's scriptures., 2017)
The Pentateuch is the heart of the Hebrew Bible and the foundational document of Judaism. It is also the focus of tremendous scholarly debate regarding the complex history of its composition, the historical background for its primeval history, ancestry narratives, and laws, the theological purposes of its final redaction, and its diverse interpretation in communities today. This textbook introduces students to the contents of the Torah and orients them to the key interpretive questions and methods shaping contemporary scholarship, inviting readers into the work of interpretation today.